2021
DOI: 10.3389/fonc.2021.629974
|View full text |Cite|
|
Sign up to set email alerts
|

DDX19A Promotes Metastasis of Cervical Squamous Cell Carcinoma by Inducing NOX1-Mediated ROS Production

Abstract: The major obstacle to treat cervical squamous cell carcinoma (CSCC) is the high prevalence of metastasis, which severely affects 5-year survival rate and quality of life for cancer patients. The DEAD-box helicase family has been reported to be a critical mediator in the development and metastasis of various cancers. DEAD-box helicase 19A (DDX19A) is a member of the DEAD-box helicase family; however, its functional role in CSCC is unclear. In this study, bioinformatics analysis of clinical samples from public d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…RT-PCR and IHC analyses confirmed the significant overexpression of NOX1 in cervical cancer compared with adjacent normal tissues. Similar results based on tissue microarray immunohistochemical staining were reported by Jiang et al [ 6 ]. Data from Transwell and scratch experiments showed a strong association of NOX1 overexpression with enhanced invasion and migration of HeLa cells, consistent with earlier findings by Jiang et al [ 6 ] that NOX1 promotes the invasion and migration of SiHa and HCC94 cell lines.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…RT-PCR and IHC analyses confirmed the significant overexpression of NOX1 in cervical cancer compared with adjacent normal tissues. Similar results based on tissue microarray immunohistochemical staining were reported by Jiang et al [ 6 ]. Data from Transwell and scratch experiments showed a strong association of NOX1 overexpression with enhanced invasion and migration of HeLa cells, consistent with earlier findings by Jiang et al [ 6 ] that NOX1 promotes the invasion and migration of SiHa and HCC94 cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results based on tissue microarray immunohistochemical staining were reported by Jiang et al [ 6 ]. Data from Transwell and scratch experiments showed a strong association of NOX1 overexpression with enhanced invasion and migration of HeLa cells, consistent with earlier findings by Jiang et al [ 6 ] that NOX1 promotes the invasion and migration of SiHa and HCC94 cell lines. Furthermore, overexpression of NOX1 promoted HeLa cell growth in vivo, supporting its carcinogenic role in cervical cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…DDX19A (chr16: 70,390,764–70,407,281 at a length of 16,518 bp) is a member of the DEAD-box family. A previous study has shown that DDX19A is overexpressed in cervical squamous cell carcinoma and promotes cell invasion and migration by inducing productions of reactive oxygen species [ 40 ]. DDX19A is identified as a prognostic factor of breast cancer disease progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA helicases involved in RNA metabolic process including transcription, RNA transport, RNA degradation [60] overexpressed in CSCC [60], BC cell lines [61] PT induces EMT [60] promotes cell migration, invasion, metastasis, NOX1 expression and ROS production [60] GPI Glucose-6-phosphate isomerase/neuroleukin cytoplasmic glycolytic-related enzyme, secreted in ECM of cancer cells it is called autocrine motility factor (AMF) [62] and functions as a cytokine or growth factor [63] overexpressed in BC [63], LUAD/NSCLC, glioblastoma, ccRCC [64], GC [62] PT REACTOME_GLUCONEOGENESIS;…”
Section: Ptbp1/hnrnp1mentioning
confidence: 99%